Question
= Graphs and Functions Composition of two functions: Basic Suppose that the functions \( q \) and \( r \) are defined as follows. \[ \begin{array}{l}q(x)=3 x-2 \\ r(x)=4 x+5 \\ (r \circ q)(-1)=\square\end{array} \] Find the following. \( (q \circ r)(-1)=\square \)
Ask by Murray Morrison. in the United States
Feb 03,2025
Real Tutor Solution
Tutor-Verified Answer
Answer
\((q \circ r)(-1) = 1\)
Solution
To find \((q \circ r)(-1)\), we'll follow these steps:
1. **Understand the Composition:**
The composition \((q \circ r)(x)\) means \( q(r(x)) \). So, we first apply \( r \) to \( x \), and then apply \( q \) to the result of \( r(x) \).
2. **Compute \( r(-1) \):**
Given \( r(x) = 4x + 5 \), substitute \( x = -1 \):
\[
r(-1) = 4(-1) + 5 = -4 + 5 = 1
\]
3. **Compute \( q(r(-1)) = q(1) \):**
Given \( q(x) = 3x - 2 \), substitute \( x = 1 \):
\[
q(1) = 3(1) - 2 = 3 - 2 = 1
\]
4. **Final Answer:**
\[
(q \circ r)(-1) = q(r(-1)) = q(1) = 1
\]
**Therefore,**
\[
(q \circ r)(-1) = 1
\]
Reviewed and approved by the UpStudy tutoring team
Like
error msg
Explain
Simplify this solution
Mind Expander
To find \((r \circ q)(-1)\), we first need to compute \(q(-1)\): \[ q(-1) = 3(-1) - 2 = -3 - 2 = -5. \] Now, we substitute this result into \(r(x)\): \[ r(q(-1)) = r(-5) = 4(-5) + 5 = -20 + 5 = -15. \] Thus, \((r \circ q)(-1) = -15\). Next, to find \((q \circ r)(-1)\), we start by computing \(r(-1)\): \[ r(-1) = 4(-1) + 5 = -4 + 5 = 1. \] Now, we substitute this result into \(q(x)\): \[ q(r(-1)) = q(1) = 3(1) - 2 = 3 - 2 = 1. \] Thus, \((q \circ r)(-1) = 1\). So, the answers are: \((r \circ q)(-1) = -15\) and \((q \circ r)(-1) = 1\).